Modeling nonsegmented negative-strand RNA virus (NNSV) transcription with ejective polymerase collisions and biased diffusion - Piedra, Felipe-Andrés; Henke, David; Rajan, Anubama; Muzny, Donna M.; Doddapaneni, Harsha; Menon, Vipin K.; Hoffman, Kristi L.; Ross, Matthew C.; Javornik Cregeen, Sara J.; Metcalf, Ginger; Gibbs, Richard A.; Petrosino, Joseph F.; et al. (Frontiers in Molecular Biosciences, 2023)
Infections by nonsegmented negative-strand RNA viruses (NNSV) are widely thought to entail gradient gene expression from the well-established existence of a single promoter at the 3’ end of the viral genome and the assumption of constant transcriptional attenuation between genes. But multiple recent studies show viral mRNA levels in infections by respiratory syncytial virus (RSV), a major human pathogen and member of NNSV, that are inconsistent with a simple gradient. Here we integrate known and newly predicted phenomena into a biophysically reasonable model of NNSV transcription. Our model succeeds in capturing published observations of RSV and vesicular stomatitis virus (VSV) mRNA levels. We therefore propose a novel understanding of NNSV transcription based on the possibility of ejective polymerase-polymerase collisions and, in the case of RSV, biased polymerase diffusion.